Pengaruh Auksin terhadap Ulat Grayak (Spodoptera litura Fabricius) serta Pertumbuhan dan Hasil Kentang Kultivar Granola: english - Hakim, Arief Lukmanul; Mutakin, Jenal; Fajarfika, Resti (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2019)
This research was purposed to determine the best auxin concentration against cluster caterpillar attack (Spodoptera litura Fabricius.), growth, and yield of potato (Solanum tuberosum Linnaeus). The research was conducted in Cikeris Cikandang, Cikajang, Garut, with altitude 1.298 meters above sea level in January until April 2018. The method used in this research was experimental method, Randomized Block Design (RBD) with 5 treatments of auxin (A = 0 ml/l, B = 1 ml/l, C = 2 ml/l, D = 3 ml/l and E = 4 ml/l) and 5 replications. The results of this research showed that the application of auxin did not affect the existence and attack of cluster caterpillar, but it affected the growth and yield of potato. The auxin concentration of 2 ml/l became the best concentration to plant height, tuber number, and tuber weight.